Clinical and hematological factors predicting the effectiveness of ruxolitinib in primary and secondary myelofibrosis. Results of a prospective single-center study - O. Yu. Vinogradova; M. M. Pankraskina; A. L. Neverova; D. I. Shikhbabaeva; M. A. Murzabekova; M. V. Chernikov; A. V. Popova; V. P. Kosenkova; L. B. Egoryan; V. V. Ptushkin (Онкогематология)
Background. Currently, targeted therapy is the most promising for the treatment of myelofibrosis (MF). Today, the results of many years of experience with the use of ruxolitinib, including outside randomized trials and the identification of predictors of its effectiveness are important.Aim. To evaluate the results of long-term ruxolitinib therapy in patients with primary and secondary MF resistant to standard treatment and compare the effectiveness of MF targeted therapy in patient groups depending on age, gender, clinical, laboratory and morphological parameters.Materials and methods. The prospective study included 206 patients (95 (46 %) men and 111 (54 %) women aged 18–84 (mean 64) years) with MF in the chronic phase who received ruxolitinib: 154 (75 %) with primary MF, 39 (19 %) – with post-polycythemic, 13 (6 %) – with post-thrombocythemic. The median duration of chronic myeloproliferative disease from diagnosisto prescription of ruxolitinib was 75 (1–432) months. According to DIPSS (Dynamic International Prognostic Scoring System), 15 % of patients were classified as high risk, 35 % as intermediate-2, 33 % as intermediate-1, and 17 % as low-risk. 44 % of patients had MF3, 49 % – MF2, 7 % – MF1. 71 % of patients had JAK2 V617F mutation, 3 % – MPL, 19 % – CALR, and in 7 % triple negative status was detected.Results. The median duration of ruxolitinib therapy was 24 (1–116) months. Clinical and hematological response at 1 month: complete and partial response – 14 %, clinical improvement – 20 %, stabilization – 57 %; at 3 months – 21, 34, 36 %, at 1 year – 34, 21, 34 %, respectively. No response was obtained in 18 % of patients. The median allele burden of JAK2 V617F during observation decreased more than twice from the initial value in half of the patients. The median of progression-free survival (PFS) from the start of ruxolitinib therapy was 28 months, the median of overall survival (OS) has not been achieved. PFS at 1 year of treatment was 68 %, at 2 years – 56 %, at 3 years – 46 %, at 5 years – 32 %, OS – 87, 75, 68, and 54 %, respectively. Among many factors analyzed before starting ruxolitinib therapy, the following ones had statistically proofed significance for PFS: age, DIPSS risk level,therapy with hydroxycarbamide, interferon, white blood cell count, platelet count, hemoglobin level, and degree of fibrosis. For OS,the following factors were significantly important: age, risk level according to DIPSS,type of MF, interferon therapy, white blood cell count, platelet count, hemoglobin level, and degree of fibrosis.Conclusion. The long-term effectiveness of ruxolitinib therapy for primary and secondary MF has been demonstrated. Gender, age, clinical, laboratory, and morphological prognostic factors of ruxolitinib therapy efficiency in MF have been identified.